PENGARUH LATIHAN PLYOMETRICS STAR JUMP TERHADAP POWER OTOT TUNGKAI ATLET TIM JUNIOR PALAPA BOLA VOLI DURI - Rahmat Syarif; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that athletes do not yet have maximal limb muscle power, the result of a not so high jump when doing jump service, blocking, and smash. Then the position of the hand when hitting the ball is still not right, so that the smash is done just to miss the ball being hit from the net. The player's jump in doing a smash is not high enough, so the athlete has difficulty directing a hard punch towards the opposing field. The purpose of this study was to determine the effect of plyometrics star jump training on the power of the athletes' leg muscles Palapa Junior Volley Ball Team Duri. The population and samples in this study were the 10 teams of the Palapa Junior Volley Ball Team Duri. The instrument used to collect data is the pre test and postal test of leg muscle explosive power with a vertical jump test. The data analysis technique used is the t test. Based on the results of the pree test and the athlete's straight jump post test for the Palapa Junior Volley Ball Team Duri there was an average increase of 14.89% with the t test that thitung = 12,531> of t table = 1,833. So it can be concluded that there is a significant effect of star jump plyometrics training on limb muscle explosive power on Palapa Junior Volley Ball Team Duri.Key Words: Plyometrics Star Jump, Power Muscle